TRANSLATION AND ADAPTATION OF ANGER MANAGEMENT/THINKING ERROR CORRECTION SECTION OF THE EQUIP PROGRAM: A QUASI EXPERIMENT TO ASSESS THE CHANGE IN AGGRESSION LEVEL AND COGNITIVE DISTORTION - HAQ, DR SADIA; SHAHED, DR SARAH; QURAISHI, DR UZMA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The present study aims to translate and adapt an anger management/thinking error correction section of the EQUIP program to reduce aggression levels and improve thinking errors among juvenile delinquent and runaway adolescents. Through the purposive sampling technique, a sample of juvenile delinquents and runaway adolescents (N = 10; M = 7, F = 3) was taken from a rehabilitation center working for the betterment of abused children in Lahore, Punjab, Pakistan. Urdu translated versions of the Reactive-Proactive Aggression Scale (Raine et al., 2006) and the How I Think Questionnaire (Barriga et al., 2001) were used as pre-test and post-test level observations to evaluate the differences between changes before and after the implementation of a specific curriculum. Results of the Wilcoxon Signed-Rank Test revealed significant lower scores on post-level measures along reactive aggression, self-centeredness, blaming others, assuming the worst, and HIT total scores, suggesting a visible improvement in juveniles’ behavior in the form of lower levels of aggression and cognitive distortions after the introduction of the intervention plan.